The nursing shared decision making attitude scale: A translation and psychometric evaluation study - Stefanie van den Broek; Floor Halvorsen; Bregje Raap- van Sleuwen; Rien de Vos (Elsevier, 2024)
Background: Nurses have an increasingly important role in the 'shared decision-making' process. Knowledge about attitudes can facilitate the implementation process of the different roles of nurses in shared decision-making. However, no specific instrument is available in Dutch to assess Dutch nurses' attitudes towards shared decision-making. Aim: This study aims to translate the Nursing Shared Decision Attitude scale into Dutch and evaluate its psychometric properties. Design: Psychometric evaluation study. Settings: A general hospital in the Netherlands. Participants: A random sample of 128 nurses. Methods: The translation was performed using translation and cross-cultural guidelines. Experts assessed content validity. In a cross-sectional study, 128 nurses completed the Dutch Nursing Shared Decision Attitude scale. The factor structure of the Dutch Nursing Shared Decision Attitude scale was determined by principal components analysis. Internal consistency and standard error of measurement (SEM) were assessed. A first and simple hypothesis for construct validity was tested. Results: Experts rated content validity as adequate. The principal components analysis revealed a 2-factor structure as most suitable (Empathic communication and Mastery learning) consistent with the original Nursing Shared Decision Attitude scale. The explained variance was 55 %. The internal consistency was 0.84 and 0.78 for the subscales and the SEM was 1,65. The mean score on the Dutch Nursing Shared Decision Attitude scale was 46,4 (CI: 42.77-49.23). A first and simple hypothesis that more experience in shared decision-making would lead to higher shared decision-making scores on the Dutch Nursing Shared Decision Attitude scale, could not be confirmed. Conclusion and innovation: This study fills in a gap concerning available instruments to assess attitudes towards SDM among nurses since there is no instrument available for the Dutch population.The results of this study are a first and somewhat promising step towards further developing the reliability and validity of the Dutch Nursing Shared Decision Attitude scale as a measure of hospital nurses' attitudes towards shared decision-making. Such measurement information is relevant to researchers and nurses involved in the implementation of shared decision-making in nursing practice.